INTEGRASI NILAI SPIRITUAL DAN KOMUNIKASI TRIRELASI DALAM PENGASUHAN DIGITAL ISLAMI: STUDI KASUS DI SD AL QURAN AR RAUDHAH LHOKSEUMAWE- ACEH - Hamdani; Hidayatus Sholihah (LPPM STAI Muhammadiyah Probolinggo, 2026)
The digital era presents challenges for Muslim families in harmonizing Islamic values with children's gadget use. This study aims to develop an Islamic digital parenting model based on empirical strategies and tri-relational communication (parent–child, child–child, nuclear–extended family) to strengthen children's Qur'anic character. This qualitative study employed an instrumental case study design involving five parents of students at SD Al-Qur'an Ar Raudhah, Lhokseumawe, selected purposively. Data were collected through semi-structured interviews, participatory observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña model with source triangulation. Five main strategies were identified: integration of worship as gadget boundaries, parental control and digital agreements, gadgets as rewards for Qur'anic memorization, exclusive Islamic content, and daily viewing history reporting. The art of tri-relational communication includes qaulan layyinan (gentle speech), sibling deliberation, evening sharing sessions, and extended family activities such as mobile recitations. This study produces the IMAN-TRI model (Integration of Worship, Active Mediation, Tri-relational Advice) which combines parental mediation theory with Islamic communication values and extended family involvement. Unlike conventional approaches, this model emphasizes collective spiritual internalization. The IMAN-TRI model can guide Muslim parents, Islamic religious teachers, and school administrators. The study recommends wider-scale model testing using a pretest-posttest design.